Study of HOTAIR LncRNA in AML patients in context to FLT3-ITD and NPM1 mutations status - Mona Salah (Egyptian Journal of Medical Human Genetics, 2021)
Abstract Background Long non-coding RNAs (LncRNAs) have recently been considered promising biomarkers for oncogenesis due to their epigenetic regulatory effects. HOTAIR is one of the oncogenic LncRNAs that was previously studied in different non-hematological malignancies. The current study set out to detect the expression level of HOTAIR LncRNA in AML patients concerning their clinical characteristics, laboratory data, FLT3-ITD, and NPM1 mutations, as well as treatment outcome. This study included quantitative detection of HOTAIR gene expression in 47 cases of AML using quantitative reverse transcription polymerase chain reaction, as well as NPM1 and FLT3-ITD genotyping. Results The HOTAIR expression was significantly higher in AML patients 6.87 (0.001) than in normal controls 1.66 (0.004–6.82) (p 0.007). The HOTAIR expression level was affected by chemotherapy, and it was correlated to hemoglobin level (p 0.001), age, total leukocytic count (p 0.022), and NPM1 mutation (p 0.017). HOTAIR gene expression level showed a correlation to relapse-free survival in the study group (p 0.04). Conclusion HOTAIR is overexpressed in patients with acute myeloid leukemia (AML). HOTAIR pre-treatment and post-chemotherapy gene expression levels can predict chemosensitivity and relapse.